MALARIA ENDEMICITY EFFECT ON COVID-19 PATHOPHYSIOLOGY: AN IN-SILICO PROTEIN-PROTEIN INTERACTION ANALYSIS - Parsa, Shima; Hatami, Naser; Sadeghinikoo, Alireza; Abolghazi, Ahmad; Kalani, Navid; Javdani, Farshid; Hashemi, Seyyed Abbas; Keshavarz, Pouyan; Avazpour, Afshin; Forouzesh, Mehdi; Doroudchi, Alireza; Zarenezhad, Mohammad (Journal of Ayub Medical College Abbottabad, 2021)
The lower spread of COVID-19 in malaria endemic regions of world has been concluded in recent global COVID-19 data analysis. Scientists have compiled hypotheses about the relationships of these two infectious diseases; while some of those seem that have fully failed as malaria medications like Hydroxychloroquine were not effective in COVID-19 prevention. Our analysis of competition between ACE2 binding proteins as well as neutulizing SARS-Cov-2 antibodies revealed a similar structure to SARS-CoV-2 spike S1 protein in Plasmodium falciparum. Surprisingly, in an In-silico protein-protein interaction analysis, 20S proteasome alpha-4 subunit of Plasmodium falciparum had a better or equal binding affinity to ACE2 protein than SARS-CoV-2, based on a computational docking and MM/GBSA analysis. We hypothesized that prior encounter with Plasmodium falciparum in malaria endemic areas and the presence of asymptomatic variants of malaria in the body may render the human body to a competitive environment for SARS-CoV-2, as both infectious agents of malaria and SARS-Cov-2 may have a strong binding affinity to ACE2 protein. Keywords: malaria; COVID-19; Protein-Protein Interaction; vaccination